Prevalence of Enterobacteriaceae in Table Eggs with Particular Reference to Enterovirulent Escherichia coli Strains - AL-Ashmawy , Maha A.M. (International Journal of Poultry Science, 2013)
A survey of the microbial quality based on enterobacteriaceae counts of the table eggs sold in Egyptian markets was conducted to evaluate their quality and the possibility of presence of Enterovirulent Escherichia coli strains. Six hundred random table egg samples were collected from different shops, supermarkets and homes. Each six pooled eggs constituted a composite sample. Higher enterobacteriaceae count/g was recorded in the content (1.1x102, 7.9x10) and in the shell (1.2x102, 2.6x102) log10 cfu/g of Baladi hen and Duck eggs respectively. Lower enterobacteriaceae counts in brown shell and white shell hen eggs (4.9x10, 6.3x10 log10 cfu/g) in the content and the shell of both types. Twenty (%) of white shell and brown shell, 20, 36% of baladi hen eggs; and 36, 68% of duck eggs (content and shell) were marginally exceeded the maximum permissible count of enterobacteriaceae by European Communities Standards. Escherichia coli, Enterobacter, Citrobacter, Klebsiella, Protus, Providencia and Shigella had been recovered from the content and the shell of different types of table eggs. E. coli strains isolated from different types of table eggs were serotyped into 7 different serotypes included O44, O111, O114, O125, O126, O127 and O128. Most of these isolates (37/39) were stx2 positive. Interstingly, all stx2 positive isolates were negative for stx1 and eae genes. Enterobacteriacae count limits should be added to the microbiological criteria for fresh table eggs as regulation in Egyptian standards. Hygienic measures should applied in home produced hen and duck eggs to lower bacterial load in egg shell and subsequently in egg content.